2011
DOI: 10.1111/j.1745-4557.2011.00418.x
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Addition of Defatted Blackcurrant Seeds on Pro-Health Constituents and Texture of Cereal Extrudates

Abstract: Extrudates used in the study were prepared on the base of cornmeal (100%)control, which was in 10, 30 and 50% replaced by defatted seeds of blackcurrant, which were a by-product of supercritical fluid extraction, used for oil production. The aim of the study was to check the influence of the level of defatted blackcurrant seeds, on texture and chemical composition of the obtained extrudates. Special attention was paid to pro-health constituents, i.e., dietary fiber, polyphenols, flavonoids and anthocyanins. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 34 publications
0
25
0
Order By: Relevance
“…This has been demonstrated in corn and rye–corn extrudates with defatted blackcurrant seeds added (Gumul et al . ). Preparation of this type of cereal‐and‐fruit extruded snack product seems to be quite promising because it can enrich the range of extruded products on this highly competitive market.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…This has been demonstrated in corn and rye–corn extrudates with defatted blackcurrant seeds added (Gumul et al . ). Preparation of this type of cereal‐and‐fruit extruded snack product seems to be quite promising because it can enrich the range of extruded products on this highly competitive market.…”
Section: Introductionmentioning
confidence: 97%
“…The attractiveness of these products is not only affected by their health‐promoting qualities (Gumul et al . ) but also by their hardness and other physical properties, because all these factors influence sensory evaluation. Among the chemical compounds responsible for establishing these properties, starch and dietary fiber (hemicelluloses and beta‐glucans) are especially important.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nutrition studies showed that an addition of BSG exerted beneficial health-promoting effects, connected with an increase in faecal mass and shortening of the time of food passage through the alimentary tract [Fastnaught, 2001]. There are many reports on dietary fibre content changes as the effect of extrusion [Fornal et al, 1993;Gumul et al, 2011;Matusz-Mirlak et al, 2007;Rzedzicki & Zarzycki, 2007]. These studies refer mainly to soluble and insoluble dietary fibre, with no differentiation into their individual fractions.…”
Section: Introductionmentioning
confidence: 99%
“…The protective effect of whole grains could be due to the presence of a number of phytochemicals, dietary fiber and phenolic compounds that may play a major role in disease risk reduction (Gumul et al . ; Gamel and Abdel‐Aal ).…”
Section: Introductionmentioning
confidence: 99%